The Role of Ki Hajar Dewantara's Tri No and Tri Nga Philosophy as the Foundation of Education for Indonesia's Golden Generation - Sylvia, Aurellia Agatha; Sujarwanto, Sujarwanto; Wijiastuti, Asri; Pamuji, Pamuji; Widajati, Wiwik; Trihantoyo, Syunu (Universitas Negeri Malang, 2025)
Education is one of the most important aspects in building Indonesia's golden generation. Ki Hajar Dewantara's philosophy, with its concepts of Tri No and Tri Nga, provides a strong foundation for emphasizing the importance of developing a complete Indonesian generation that is cultured, civilized, and of superior quality. This article aims to analyze the role of Ki Hajar Dewantara's Tri No and Tri Nga philosophy as the foundation of education in creating Indonesia's golden generation. These concepts will be explained in the context of the Second Principle of Pancasila (Just and Civilized Humanity), which emphasizes the importance of creating diversity awareness and a sense of togetherness. This study uses a literature review approach to explore a deeper understanding of Ki Hajar Dewantara's contribution to education in Indonesia. The combination of Ki Hajar Dewantara's Tri No and Tri Nga philosophies results in three important stages in shaping the foundation and character of children's education. Ki Hajar Dewantara's Tri No and Tri Nga educational philosophies are an important foundation for the formation of individuals with character, morals, and the ability to live harmoniously in a diverse society, which is the core of the Second Principle of Pancasila. This philosophy promotes learning that not only enhances academic intelligence but also character development.